A disciplina de cálculo diferencial e integral na perspectiva da pós-graduação em educação e educação matemática: um balanço das produções acadêmicas brasileiras - Pontes Junior, Antonio Carlos Fonseca (Universidade Federal de São Carlos, 2021)
This work aims to identify and characterize the perspective of the work developed in Graduate Programs in Education and Mathematics Education (ME) through the realization of a systematic mapping (MS) on the discipline of Differential and Integral Calculus (CDI) and its teaching. For the realization of the MS, it will be considered as database dissertations and theses of the programs mentioned above in the Brazilian Digital Library of Dissertations and Theses (BDTD) and in the CAPES Theses & Dissertations Catalog (BTD). The research was based on the search for answers to the question: How the CDI discipline (and its teaching) is idealized/perceived/worked on by the academic researches produced in Graduate Programs in Education and ME? The research methodology is qualitative and to carry out the MS, the concepts of mapping and systematic review by Falbo et al. (2017) and Melo (2006, 2013). In the initial mapping, on the teaching of CDI, 67 publications were selected that focused on teaching/learning Calculus. After categorization, 5 axes were found, which we called: 1) Epistemological analysis on the teaching of Calculus; 2) Historical analysis of the teaching of Calculus; 3) The Calculus teacher; 4) Learning from/in Calculus; and 5) Mapping of Calculus. In a second moment, 96 more works are added, totaling 163 analyzed dissertation and theses. The main results identified the growing trend of Education and MS to discuss the teaching of CDI from 1999 and, in general, having the main axis in the Learning of/in Calculus, in general, or with the application of some methodology and/or using some technology that is not traditional in teaching. In addition, one can see a preeminent gap in the discussion of the teacher who Teach Calculus, with less than 10% of the publications focused on this theme and on Inclusive Education in the teaching of CDI.
The discipline of differential and integral calculus from the perspective of postgraduate studies in education and mathematics education: a review of Brazilian academic productions
Keywords: Ensino de cálculo; Mapeamento sistemático; Disciplina de cálculo diferencial e integral; Teaching of calculus; Systematic mapping; Differential and integral calculus discipline; CIENCIAS HUMANAS::EDUCACAO